Institutes of the Christian religion ; v. 2 - Calvin, John 1509-1564; Battles, Ford Lewis, 1915-1979; McNeill, John Thomas, 1885-1975 (Philadelphia, PA Westminster, 1983)
Contents : v. 2 : Books 3:20 - 4:20. Includes bibliographical references and indexes.
Originally published 1536
Keywords: Calvin, John -- 1509-1564 -- Reformer; Church history -- Reformation -- writings